Examining the Interplay Between Islamic Education and Science Domains in Morocco's Educational Policy - Fariq, Wan Muhammad; Karim, Nazir; Helmiati, Helmiati (Graduate Program, Universitas Islam Darussalam (UID) | Islamic University of Darussalam, 2023)
King Mohammed VI bestowed special emphasis upon Morocco, a country with a population of 30 million people and a Muslim majority of 99%. In 1999, Moroccan students’ performance in mathematics and science fell below the global average. The education system in Morocco is perceived as being unresponsive to the demands of the labour market, prompting the implementation of the National Education Emergency Support Programme in 2009. This study aims to examine the educational policies established by the Moroccan government. This research involves conducting a literature review, specifically employing content analysis tools. Research findings indicate that the majority of Islamic schools or madrasas in Morocco are predominantly overseen by autonomous or privately-owned organisations. The government’s involvement is necessary to promote the development of these schools in alignment with the requirements of the labour market, particularly in the realm of science.